Elimination half-life may explain the relative efficacy of boceprevir and telaprevir in the treatment of hepatitis c virus genotype 1 - KIERAN, JENNIFER (My University, 2013)
Background. The licensing of direct-acting antivirals heralds a new era in the treatment of hepatitis C virus (HCV) genotype 1. We undertook a mixed treatment comparison to examine the relative efficacy among current treatments for HCV. Methods. A systematic literature review identified relevant studies. Meta-analyses were planned in treatment-naive and treatment-experienced patients. Study arms that evaluated telaprevir or boceprevir for unlicensed durations or without both pegylated interferon and ribavirin at standard doses were excluded. A Bayesian mixed treatment comparison model was fitted for each patient population. Results. Four hundred ninety-nine studies were identified. Ten met inclusion criteria. In the subgroup of prior treatment “relapsers,” telaprevir had greater relative efficacy than boceprevir (odds ratio [OR], 2.61 [95% confidence interval {CI}, 1.24–5.52]). There were no statistically significant differences detected in relative efficacy for other patient categories. Treatment-naive patients: boceprevir vs standard of care (n = 1417) (OR, 3.06 [95% CI, 2.43–3.87]); telaprevir vs standard of care (n = 1309) (OR, 3.24 [95% CI, 2.56–4.10]); telaprevir vs boceprevir (OR, 1.06 [95% CI, 0.75–1.47]). Total treatment-experienced population: boceprevir vs standard of care (n = 604) (OR, 6.53 [95% CI, 4.20–10.32]); telaprevir vs standard of care (n = 891) (OR, 8.32 [5.69–12.36]); telaprevir vs boceprevir (OR, 1.27 [95% CI, .71–2.30]). Conclusions. Telaprevir had greater relative efficacy than boceprevir in patients who had previously relapsed. There was insufficient evidence to detect a difference in treatment outcomes between the 2 agents in the overall population. It was not possible to determine relative efficacy for subgroups such as patients with cirrhosis owing to small numbers.
PUBLISHED
Keywords: Bayesian meta-analysis HCV protease inhibitors Ireland hepatitis C; Bayesian meta-analysis HCV protease inhibitors Ireland hepatitis C